« Pour l’honneur des travailleurs » : les Gilets jaunes face au mépris de classe - Clara Lucas (Sociologies)
The lyrics of the anthem of the Yellow Vests movement of 2018 in France, makes it a struggle “for the honor of workers”. Taking workers’ honour by its shortcoming, contempt, this article examines, on the basis of a qualitative survey, the way in which emotions help to produce social stratification and awareness of one’s place in it, awareness that, depending on the context, can also be at the source of strategies of adaptation, resistance and engagement in collective action. The focus on moral sentiments, which coordinate, in ordinary time and then in collective action, a political agency, thus enables us to apprehend how, for these subordinate workers, structural and subjective logics come together in the relationship to protest engagement.